PENGARUH PENERBITAN OBLIGASI SYARIAH (SUKUK) PERUSAHAAN TERHADAP REAKSI PASAR PADA PERUSAHAAN-PERUSAHAAN YANG MENERBITKAN OBLIGASI SYARIAH TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Dewi Kurnia Sari; Noor Shodiq Askandar; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2017)
0px; "> ABSTRACTThe purpose of this research is 1). To determine the influence of the value andrating issuance of Islamic bonds (sukuk ) market reaction to the company (cumulativeabnormal return ) ,2). To find out how the value and rating issuance of Islamic bonds(sukuk) market reaction to the company (cumulative abnormal return ).By using population 230 publishing and samples 38 publishing all companieslisted in Indonesia Stock Exchange in 2012-2016 . Data collection methods used inthis research is the method of documentation . Methods of data analysis used in thisstudy include: normality test , classic assumption test , multiple linear regressionanalysis , simultaneous test (F) , partial test (t) , and the coefficient of determination .The results were obtained : (1) The value of the issuance of Islamic bonds with a 0.05significance level is is (-1.690 ≤ -0.899 ≤ 1.690). (2) Rating the issuance of Islamicbonds is 0.05 significance level is (-1.690 ≤ -1.831 ≤ 1.690).Based on the above results , it can be concluded that the simultaneous andpartially variable Value and Rating issuance of Islamic bonds (sukuk) did not affectthe market reaction ( cumulative abnormal stock return) . 2Keywords : Value issuance of Islamic bonds , Rating issuance of bonds , the market reaction (cumulative abnormal return )